537 Video-based school children road injury prevention tool (V-SCRIPT) in Karachi: quasi-experimental study. (20th November 2022) - Khan, Uzma Rahim; Ali, Asrar; Khudadad, Umerdad; Masud, Sarwat; Ahmed, Afzal; Farooq, Mohammad Umer
Abstract : Background: Road traffic injuries (RTIs) are a major public health concern for children. They are particularly less skilled in perceiving road hazards and are unable to take appreciate safety precautions as road-users. Traffic hazard perception training is a promising intervention to improve the safety skills of this vulnerable group. Aims: This study aims to design and implement an interactive web-based hazard perception tool and assess the feasibility of the application in improving the ability to detect road-hazards among children in Karachi, Pakistan using recorded road traffic scenarios. Methods: It is a Quasi-experimental design to evaluate the effectiveness of the intervention with outcome measurement of hazard detection score and scoring of correct safety actions taken by the web users. The study will be piloted in public and private schools of Karachi Pakistan by enrolling 500 children from grade 8th to 10th. Results: We have recorded 12 real-world traffic hazard scenarios with corrected safety measures acted by the children as pedestrians, riders of motorcycles and bicycles, and occupants of cars, and buses. The interactive website named Roadwhiz is under the development phase and is expected to be completed by May 2022. We have video recorded actor children performing scripted road hazards and following safety regulations such as using sidewalks and crossing the road using zebra-crossing. These scenarios were developed based on literature review, consultation with local traffic authorities, field observations, and brainstorming sessions with the research team and children to script contextual hazards and safety measures to be taken according to Karachi city's traffic hazards. Conclusion: RTIs is a major injury and death burden among children and training their traffic hazard perception may help in preventing these injuries. Interactive web-based training tools can be engaging and promote traffic safety learning outcomes among children. Further studies are needed to investigate the validity and effectiveness of these tools. Learning Outcomes: This project gave us a multidisciplinary experience to effectively work as a team in addressing a common public health concern (injury prevention among children) by engaging experts from information technology, videography, traffic authorities, engineering, urban planners, the education sector, and public health practitioners.